When bones meet blood vessels: BMP-2 expression and vascular calcification in a rat model of metabolic syndrome - Sihotang, Fransiska Anggreni; Rohman, Muhammad Saifur; Satrijo, Budi; Sargowo, Djanggan; Rizal, Ardian (Heart Science Journal, 2026)
Background: Vascular calcification (VC) is a significant contributor to cardiovascular morbidity, particularly in conditions like metabolic syndrome (MetS). Bone Morphogenetic Protein-2 (BMP-2) is implicated in the osteogenic differentiation of vascular cells, potentially linking MetS to VC. Objective: This study aimed to investigate aortic BMP-2 expression and the presence of VC in a rat model of MetS and assess the effects of Metformin, Empagliflozin, and a green tea/green coffee extract combination. Methods: Male Sprague-Dawley rats were induced with MetS using a high-fat, high-sucrose diet combined with a low-dose streptozotocin injection (30 mg/kgBW). Rats were divided into five groups (n=5): Normal control (NORM), MetS (METS), MetS + Metformin (MFN, 500 mg/kgBW), MetS + Empagliflozin (EMP, 30 mg/kgBW), and MetS + GTCE (300 mg/kgBW green tea + 200 mg/kgBW green coffee). Treatments were administered daily via oral gavage for 9 weeks. Result: Aortic tissue was collected for histological analysis and qRT-PCR to measure relative BMP-2 mRNA expression. Histological analysis revealed calcification in the aortic wall of the METS group rats. Compared to the NORM group, BMP-2 mRNA expression was significantly upregulated in the METS group (p<0.001). Treatment with MFN, EMP, and GTCE significantly downregulated BMP-2 mRNA expression compared to the METS group (p<0.001 for all). Conclusion: This study demonstrates that MetS induction in this rat model might promotes aortic calcification and significantly increases BMP-2 mRNA expression. Pharmacological interventions with Metformin, Empagliflozin, and green tea/coffee extract attenuated the MetS-induced upregulation of BMP-2 expression. These findings suggest a potential role for BMP-2 in MetS-associated vascular changes.